2023
DOI: 10.1111/xen.12793
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous expression of endocrine and progenitor cells within the neonatal porcine pancreatic lobes–Implications for neonatal porcine islet xenotransplantation

Abstract: Neonatal porcine islets (NPIs) are a source of islets for xenotransplantation. In the pig, the pancreatic lobes remain separate, thus, when optimizing NPI isolation, the pancreatic lobes included in the pancreatic digest should be specified. These lobes are the duodenal (DL), splenic (SL) and connecting (CL) lobe that correspond to the head, body‐tail, and uncinate process of the human pancreas. In this study we are the first to evaluate all three neonatal porcine pancreatic lobes and NPIs isolated from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(285 reference statements)
0
2
0
Order By: Relevance
“…Researchers have demonstrated the direct relationship between statins and insulin release. 14 It has also been observed that potential endocrine progenitor cells exist in the pancreatic duct walls. 15 These progenitor duct cells can form endocrine tissue not just during embryonic development but throughout life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated the direct relationship between statins and insulin release. 14 It has also been observed that potential endocrine progenitor cells exist in the pancreatic duct walls. 15 These progenitor duct cells can form endocrine tissue not just during embryonic development but throughout life.…”
Section: Discussionmentioning
confidence: 99%
“…19 Simvastatin may also inhibit the mevalonate pathway, thereby modulating insulin secretion. 14 Further studies are required to elucidate the molecular pathways involved in this process. This research makes unique contributions by specifically focusing on simvastatin's effects on islet morphology, unlike broader statin research.…”
Section: Discussionmentioning
confidence: 99%